Comparing Students’ Learning Outcomes Using Problem Based Learning Model and Inquiry Based Learning Model - Nasar, Adrianus; Kurniati, Klaudensia (Jurnal Pendidikan Fisika, 2020)
This study aims to compare science learning outcomes between students who take problem based learning (PBL) with students who take part in inquiry based learning (IBL). The method used in this study is a quasi-experimental research method with a pretest-posttest control group design. The population of this study were students of class VIII SMP Negeri 1 Kuwus 2018/2019 school year which numbered 97 students and consisted of 4 classes.  Students who followed the PBL learning model numbered 24 people and those who participated in the IBL learning model were 24 people. Data collection research was carried out using test techniques. The data was processed into normalized gain (N_gain) between posttest and pretest. Furthermore, the data is calculated using the t-test to compare the mean gain of learning outcomes between students who take part in learning using the PBL model and students who take part in learning using the IBL model. The results showed that there t value (tcount) = 2.566 with a significance (Sig. (2-tailed)) of 0.014 so it can be concluded that  were differences in learning outcomes between students who took part in learning using the PBL model and students who took part in learning using the IBL model.Keywords: Problem Based Learning, Inquiry Based Learning, Learning OutcomesPenelitian ini bertujuan membandingkan hasil belajar antara siswa yang mengikuti pembelajaran model PBL dengan siswa yang mengikuti pembelajaran model IBL. Metode yang digunakan dalam penelitian ini yaitu metode penelitian kuasi eksperimen dengan desain Control Group, Pretest–Posttest Design. Populasi dalam penelitian ini adalah siswa kelas VIII SMP Negeri 1 Kuwus tahun pelajaran 2018/2019 yang berjumlah siswa 97 orang dan terdiri dari 4 kelas. Siswa yang mengikuti model pembelajaran PBL berjumlah 24 orang dan yang mengikuti model pembelajaran IBL berjumlah 24 orang. Pengumpulan data penelitian dilakukan dengan teknik tes. Data diolah menjadi gain ternormalisasi (N_gain) antara postest dan pretest. Selanjutnya data dihitung dengan menggunakan perbedaan rerata (uji-t) untuk membandingan rerata gain (Compare Mean-Independent Sampel T Test) antara PBL dan IBL. Hasil Penelitian menunjukkan nilai t hitung (thitung) = 2,566 dengan signifikansi (Sig. (2-tailed)) sebesar 0,014 dengan demikian dapat disimpulkan bahwa ada perbedaan peningkatan hasil belajar antara siswa-siswa yang mengikuti pembelajaran menggunakan model PBL dengan siswa-siswa yang mengikuti pembelajaran menggunakan model IBL.Kata kunci: Pembelajaran Berbasis Masalah, Pembelajaran Berbasis Inkuiri, Hasil Belajar